The Integration of Bola Dansa Media (Banana Leaf Nature Puppets) and the Tri-N Approach in Indonesian Language Learning to Improve Elementary School Students’ Storytelling Skills - Heny Tafaroh; Insanul Qisti Barriyah; Akbar Al Masjid (Jurnal Ilmiah Sekolah Dasar, 2025)
Storytelling skills are a crucial aspect of Indonesian language learning, as they help students organize ideas, enrich vocabulary, and build confidence in oral communication. This study aims to analyze the effectiveness of integrating Bola Dansa media (puppets made from banana leaves) with the Tri-N approach in developing storytelling abilities of elementary school students. This research employs a qualitative descriptive method with elementary school students as the subjects. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s model, including data reduction, data display, and conclusion drawing. The results indicate an improvement in students’ storytelling skills, demonstrated by a 50.00% increase in story structure, 55.00% improvement in fluency, 45.00% enhancement in expression and intonation, and 45.00% improvement in communicative and context-appropriate language use. The Tri-N approach, through the stages of Niteni (observing), Niroake (imitating), and Nambahi (developing), effectively enhanced students’ creativity, courage, and ability to construct stories. Therefore, the integration of Bola Dansa media and the Tri-N approach is effective in developing students’ storytelling skills comprehensively, suggesting that creative media-based and reflective-stage strategies can serve as innovative alternatives in Indonesian language learning at the elementary level.